Cryopreservation of Sterlet, Acipenser ruthenus Spermatozoa: Evaluation of Quality Parameters and Fine Ultrastructure - Dadras, Hadiseh; Golpour, Amin; Rahi, Deepali; Lieskovská, Jaroslava; Dzyuba, Viktoriya; Gazo, Ievgeniia; Policar, Tomas (Frontiers in Marine Science, 2022)
The present study aimed to evaluate cryo-injury during the cryopreservation process in sterlet (Acipenser ruthenus) sperm, focusing on ultrastructural characteristics. Post-thaw sperm quality parameters, including total motility rate, curvilinear velocity (VCL), linearity (LIN), plasma membrane integrity, antioxidant status, DNA damage, and fine ultrastructure were examined on fresh and cryopreserved sperm with/without addition of a single optimal dose of AFPI (10 µg/ml). A lower motility rate, VCL and plasma membrane integrity, and increased DNA damage (p < 0.05) were observed in frozen-thawed spermatozoa with/without AFPI compared to fresh spermatozoa. The morphology and ultrastructure of spermatozoa were affected during the cryopreservation process with/without supplementation of AFPI. Morphological abnormalities were observed in mitochondria (49-54%) and flagellum (55-57%) of cryopreserved spermatozoa with/without AFPI compared to fresh spermatozoa. In conclusion, the morphology and ultrastructure of spermatozoa were slightly changed after cryopreservation of sterlet spermatozoa with/without 10 μg/mL AFPI.